A total evidence phylogeny sheds light on a new Vriesea (Tillandsioideae, Bromeliaceae) species from the Brazilian Atlantic Forest - Kessous, Igor Musauer; Salgueiro, Fabiano; da Costa, Andrea Ferreira (Plant systematics and evolution, 2024)
Vriesea is one of the most diverse genera in the Brazilian Atlantic Forest, comprising approximately 170 species in this domain. Included in this genus, the V. ensiformis group encompasses ten species that are distributed from northeastern to southern Brazil. During field expeditions in Parque Nacional da Serra dos Órgãos, Rio de Janeiro, Brazil, we found a new species which was previously long recognized as Vriesea aff. gradata in herbaria. Thus, here we aim to describe V. organensis and investigate its phylogenetic relationship to other species in the V. ensiformis group through a total evidence approach. We conducted an extensive literature review, herbarium consulting and field trips to gather data for describing the new species. Additionally, we constructed a concatenated matrix of molecular and morphological data to generate a phylogenetic hypothesis for the V. ensiformis group. Vriesea organensis is morphologically related to V. psittacina , V. gradata and V. fluviatilis and is described as possibly critically endangered. Our phylogenetic tree revealed that V. organensis is closely related to V. fluviatilis , in contrast to the herbarium hypothesis of similarity with V. gradata . The new species is characterized by the floral bracts incurvate and strongly carinate at the apex, rachis exposed when flowering, petal yellow with green apex and stigma exceeding the anthers. Furthermore, our findings indicate that the V. ensiformis group is not monophyletic based on our dataset.